ATP-Binding Cassette Systems of Brucella. (11th January 2009) - Jenner, Dominic C.; Dassa, Elie; Whatmore, Adrian M.; Atkins, Helen S.
Abstract : Brucellosis is a prevalent zoonotic disease and is endemic in the Middle East, South America, and other areas of the world. In this study, complete inventories of putative functional ABC systems of five Brucella species have been compiled and compared. ABC systems of Brucella melitensis 16M, Brucella abortus 9-941, Brucella canis RM6/66, Brucella suis 1330, and Brucella ovis 63/290 were identified and aligned. High numbers of ABC systems, particularly nutrient importers, were found in all Brucella species. However, differences in the total numbers of ABC systems were identified ( B. melitensis, 79; B. suis, 72; B. abortus 64; B. canis, 74; B. ovis, 59) as well as specific differences in the functional ABC systems of the Brucella species. Since B. ovis is not known to cause human brucellosis, functional ABC systems absent in the B. ovis genome may represent virulence factors in human brucellosis.